Intention to Do Whistleblowing of Government Internal Supervisory Apparatus at the Inspectorate of Central Java Province - Lidiarti, Andina; -, Sukirman (Accounting Analysis Journal, 2019)
The purpose of this study is to examine the effects of internal locus of control and organizational commitment in moderating the relationship of professional commitment and anticipatory socialization on the intention of whistleblowing. The population were all Government Internal Supervisory Apparatus (APIP) at the Inspectorates of Central Java as many as 55 employees. The sampling technique used saturation sampling and obtained 49 respondents. The analytical method used is Structural Equation Modeling- Partial Least Square (SEM-PLS) with the SmartPLS 3.0 analysis tool. The results show that professional commitment and anticipatory socialization partially have positive effect on the intention of whistleblowing. Internal locus of control was not able to moderate the effect of professional commitment and anticipatory socialization on the intention of whistleblowing. Organizational commitment was able to strengthen the effect of professional commitment on the intention of whistleblowing. Organizational commitment was not able to moderate the effect of anticipatory socialization on the intention of whistleblowing. The conclusions are professional commitment and anticipatory socialization affect on the intention of whistleblowing and organizational commitment can strengthen the relationship of professional commitment on the intention of whistleblowing.